(untitled) (Palíndromo, 2017)
In 2016, Street art was incorporated into the art system of the exhibitions and large exhibitions in Brazil and around the world. Its subversion potentiality was weakened by the need to meet new demands. Then how to make a Graffiti immersed in the city scenery attractive for the market? The answer is uproot it from its specific place and takes it to the museum and then to the gallery. This is not just a play on words; it has recently occurred in Europe and was contested by intellectuals, civil society and artists.